2023
DOI: 10.1186/s12961-023-00968-w
|View full text |Cite
|
Sign up to set email alerts
|

Why and how has the United Kingdom become a high producer of health inequalities research over the past 50 years? A realist explanatory case study

Abstract: Background Evidence on health inequalities has been growing over the past few decades, yet the capacity to produce research on health inequalities varies between countries worldwide and needs to be strengthened. More in-depth understanding of the sociohistorical, political and institutional processes that enable this type of research and related research capacity to be generated in different contexts is needed. A recent bibliometric analysis of the health inequalities research field found inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…First, both studies identified that the United Kingdom and Barcelona have strong traditions of public health and recognition of social justice (contextual factors), which date back to the nineteenth century. 30,32,40 In addition, evidence suggests that under certain conditions, this recognition of HI accumulated over time (contextual factor), and when potentially combined with heightened concern (mechanism), it triggered a change in certain agents' behaviors and actions, initiating a chain of events which likely led to the production of a high volume of HI research in both settings (outcome of interest).…”
Section: Insights From Two High Producers Of Health Inequalities Rese...mentioning
confidence: 99%
See 4 more Smart Citations
“…First, both studies identified that the United Kingdom and Barcelona have strong traditions of public health and recognition of social justice (contextual factors), which date back to the nineteenth century. 30,32,40 In addition, evidence suggests that under certain conditions, this recognition of HI accumulated over time (contextual factor), and when potentially combined with heightened concern (mechanism), it triggered a change in certain agents' behaviors and actions, initiating a chain of events which likely led to the production of a high volume of HI research in both settings (outcome of interest).…”
Section: Insights From Two High Producers Of Health Inequalities Rese...mentioning
confidence: 99%
“…In addition, dedicated resources must also be allocated (mechanism) to ensure a minimum level of investment in HI-related human resources via creating dedicated training programs and enabling career structures, and to create a critical mass of trained professionals who are able to work on HI (contextual factor). 24,27,30,32 During the COVID-19 pandemic, for example, several public institutions in Barcelona were able to rapidly identify inequalities in COVID-19 incidence and mortality within and between neighborhoods, partly due to the preexisting HI research infrastructure in the city. 8 Third, the strong political nature of the HI research production process emerges from both case studies, particularly the influential role of politics, and institutional and individual values (contextual factors) in activating certain mechanisms over time.…”
Section: Insights From Two High Producers Of Health Inequalities Rese...mentioning
confidence: 99%
See 3 more Smart Citations